2017
DOI: 10.1016/j.psychres.2017.01.099
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity mediates gender differences in post-concussive symptoms in a clinical sample

Abstract: Traumatic brain injury (TBI) is both prevalent and potentially disabling. Extant literature has demonstrated women to report greater post-concussive symptoms (PCS) compared to men, highlighting the necessity of investigations into malleable, gender-linked risk factors for PCS that hold promise for reducing this gender disparity. Anxiety Sensitivity (AS) and Distress Tolerance (DT) are gender-linked risk factors that may be related to PCS. Despite a breadth of research supporting elevated AS and reduced DT in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
1
26
2
Order By: Relevance
“…TBI is believed to influence PTSS via disruptions in cognitive control (i.e., cognitive dyscontrol) and exaggerated emotional reactivity (Aupperle, Melrose, Stein, & Paulus, 2012 ; Bryant et al, 2010 ; Glenn et al, 2017). As described above, AS increases both PTSS-related (Asmundson & Stapleton, 2008 ; Boffa et al, 2016 ; Taylor, 2003 ; Vujanovic, Zvolensky, & Bernstein, 2008) and TBI-related (Albanese, Boffa, Macatee, & Schmidt, 2017) symptoms of cognitive dyscontrol and arousal via the misinterpretation of these sensations as harmful. Therefore, the effects of TBI on PTSS may be potentiated among those with high AS cognitive and AS physical concerns due to the amplification of TBI-related symptoms of cognitive dyscontrol and anxious arousal, respectively.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…TBI is believed to influence PTSS via disruptions in cognitive control (i.e., cognitive dyscontrol) and exaggerated emotional reactivity (Aupperle, Melrose, Stein, & Paulus, 2012 ; Bryant et al, 2010 ; Glenn et al, 2017). As described above, AS increases both PTSS-related (Asmundson & Stapleton, 2008 ; Boffa et al, 2016 ; Taylor, 2003 ; Vujanovic, Zvolensky, & Bernstein, 2008) and TBI-related (Albanese, Boffa, Macatee, & Schmidt, 2017) symptoms of cognitive dyscontrol and arousal via the misinterpretation of these sensations as harmful. Therefore, the effects of TBI on PTSS may be potentiated among those with high AS cognitive and AS physical concerns due to the amplification of TBI-related symptoms of cognitive dyscontrol and anxious arousal, respectively.…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, the effects of TBI on PTSS may be potentiated among those with high AS cognitive and AS physical concerns due to the amplification of TBI-related symptoms of cognitive dyscontrol and anxious arousal, respectively. Indeed, Albanese et al (2017) found evidence that TBI was more strongly related to PTSS among those with elevated AS cognitive concerns. However, this study was unable to test if AS total score, physical concerns, or social concerns demonstrated similar interactive effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women have been reported elevated AS both in nonclinical [ 59 ] and clinical samples [ 95 ]. It is confirmed that patients with higher AS tends to exaggerate PCS symptoms by amplifying its severity [ 96 ].…”
Section: Main Textmentioning
confidence: 95%
“…As described above, ASCC increases PTS through the amplification of cognitive-dyscontrol symptoms of anxiety through the misinterpretation of these sensations as harmful (Asmundson & Stapleton, 2008; Boffa et al, 2016; Taylor, 2003; Vujanovic et al, 2008). Importantly, TBI is associated with similar symptoms of cognitive dyscontrol (Ryan & Warden, 2003) which may be amplified by AS (Albanese, Boffa, Macatee, & Schmidt, 2017) and are theorized to be a mechanism explaining the link between TBI and PTS (Aupperle, Melrose, Stein, & Paulus, 2012). Thus, high ASCC may increase the effect of TBI on PTS through the misinterpretation of cognitive dyscontrol symptoms as harmful, thereby amplifying emotional reactions to a trauma reminder.…”
Section: Introductionmentioning
confidence: 99%